Effects of Mechanical Activation of Precursors in The Synthesis of Ca-Doped BaTiO3 Via Conventional Solid State Reaction Method. (March 2019) - Gili, M B; Chu, R; Cervera, R
Abstract: The synthesis of pure ceramics with high degree of crystallinity is a major challenge especially in fabricating electronic devices. In this study, Ca-doped BaTiO3 with minimal impurity was successfully synthesized using conventional solid-state reaction method. The effect of mechanical activation of the precursors in the crystallinity and porosity of the material was investigated. For samples sintered at 1000 °C, the crystallite size slightly decreased from 5.410 Å to 5.288 Å which is equivalent to 2.31% reduction upon activation of precursors. At sintering temperature of 850 °C, the porosity increased from 35.985% to 39.217% with mechanical activation of the precursor powders while at 1000 °C, it jumped from 54.803% to 57.084%.